Improving Oral Case Presentations With E-Learning and Deliberate Practice - Heather Heiman; Craig Adams; Toshiko Uchida; Paul Pribaz; John Butter; Gary Martin (Association of American Medical Colleges, 2014)
Abstract Introduction Oral presentations are critically important for patient care and student assessment. Nationally and at our institution, students are frustrated by what they perceive as unclear and inconsistent expectations by faculty for their oral presentations. Yet we know that clinician-educators largely can agree on the important components of a presentation. E-learning is a way to disseminate a standard curriculum to learners, and it can include interactive components to improve retention. Deliberate practice with feedback is a highly effective way to bring students to mastery. We aimed to combine these learning techniques to improve students' confidence and competence ahead of starting their clerkships. Methods This resource consists of a curriculum and assessment materials to ensure that second- and early third-year medical students are ready to present patients in a standardized, succinct, and well-reasoned way. The curriculum requires 3-4 hours of independent student preparatory time: 1-2 hours of work with an interactive online module and 2 hours to prepare standardized cases. A total of 30 minutes of faculty, resident, or senior medical student time is needed for each curriculum student to deliver his/her presentation and receive specific feedback. Two assessment cases with associated checklists are provided. Results We evaluated 132 second-year medical students (67 in the intervention group and 65 in the control group) at three time points: prior to any student receiving the curriculum, after the intervention students had received the curriculum, and after all students had received the curriculum. After taking the curriculum, mean scores of the intervention students improved from 60.2% to 70.1%, while scores of the waitlist control students improved less, from 61.8% to 64.5%. This difference in improvement between groups was significant at p < .01. Once all students had received the curriculum, mean scores for the intervention and waitlist control students rose to 77.8% and 78.4%, respectively, as compared to 68.1% for the untrained comparison students. We also applied a mastery learning model to these presentation skills, with minimum passing scores (MPSs) established for each assessment case. In 2012, we demonstrated that 130 of 146 second year students (89%) achieved the MPS for their case at their final exam, and the other 16 students (11%) were able to achieve the MPS on reassessment after engaging in one additional deliberate practice case. Discussion The interview videos in the resource were done with efficiency in mind but are not as patient centered as they could be. There should be more empathic verbal statements from the interviewers. However, both interviewers do use effective nonverbal communication and open-ended questions. This module does not include lab results and other study results, which are a challenge for students to present along with the history and physical in the third year. It also does not include follow-up presentations or bullet presentations. We are considering creating a second part of the curriculum to include these in the future.